Enhanced microprobe endstation for high-throughput and versatile sample analysis at APS 2-ID. Issue 1 (1st December 2022) - Davis, Benjamin; Antipova, Olga; Preissner, Curt; Bean, Sunil; Holler, Mirko; Mooney, Tim; Kearney, Steven; Lai, Barry
Abstract: The new APS-U 2-ID Microprobe instrument will provide high-throughput and versatile sample analysis capabilities and will bridge the gap to higher resolution APS-U nanoprobes. Available techniques include XRF microscopy, tomography, µXANES, µSAXS, ptychography, and laminography. A very high flux of more than 10 13 photon/s is delivered across a wide range of x-ray energies from 7-20 keV. KB mirror focusing optics enable a small 50nm spot size for detailed resolution, while also providing a long working distance of 50 mm to accommodate large samples of up to 10x10 mm. The Microprobe will accommodate samples in an inert helium environment, with controlled flow of fluids, electrical biasing, and sample heating & cooling. High throughput is enabled by fast and smooth fly-scanning stages, a high-accuracy metrology system, new detectors, and upgrades in the multi-bend achromat storage ring, insertion device, 2-ID beamline, and monochromator. All these instrument upgrades will empower advancements in biological, materials and environmental sciences.